Vice-Chancellors Not Too Concerned - New Straits Times, Jennifer Gomez & Irdiani Mohd Salleh (2008)
Universiti Kebangsaan Malaysia Vice Chansellor Professor Datuk Dr Sharifah Hapsah Syed Hassan Shahabudin has been asked the same question this time of the year for the past five years.